Recent trends in the antimicrobial susceptibility patterns of urinary pathogens in type II diabetes mellitus - Gurjar, Dinesh; Mathur, Akash; Sai, Ramkrishna; Lakesar, Arvind; Saxena, Puneet (International Journal of Research in Medical Sciences, 2018)
Background: Diabetes mellitus is one of the most frequently encountered diseases in clinical practice and since the diabetic patients are at an increased risk of infections specially those of the urinary tract it is imperative for a physician to be aware of the prevalence and antibiotic susceptibility patterns of urinary pathogens. Thus, in this study we assess the recent trends in antimicrobial susceptibility patterns of urinary pathogens in type II diabetes mellitus. Methods: Ninety-three eligible type II diabetes mellitus cases without genitourinary symptoms or abnormalities along with 93 non-diabetic healthy controls were recruited. Mid-stream urine was collected after taking informed consent and each sample tested using the dipstick, microscopy and culture techniques. Isolates were identified using standard biochemical tests. Results: Prevalence of asymptomatic bacteriuria (ASB) in our study was found to be 34.4% among cases of type II diabetes mellitus while it was 6.45% among non-diabetic healthy controls. E. coli was the most common urinary pathogen isolated. E. coli susceptibility towards amikacin was 85.71%, towards ceftriaxone and nitrofurantoin was 71.73% and for meropenem and doxycycline 66.67% susceptibility was observed. In the one case where pseudomonas was cultured, it was susceptible to meropenem, gentamycin, cefoperazone-sulbactum and cefuroxime. In an isolated case where Proteus species was grown, it showed susceptibility to meropenem, norfloxacin, levofloxacin and co-trimoxazole. Enterobacter species which was grown, showed susceptibility to meropenem, vancomycin, amikacin, nitrofurantoin, norfloxacin, levofloxacin and co-trimoxazole. Gram positive bacteria mainly showed susceptibility to ceftriaxone, teicoplanin, vancomycin and doxycycline. Conclusions: The prevalence of bacteriuria is significantly higher in diabetics as compared to non-diabetics and with the recent trends suggestive of emerging resistance among urinary pathogens to some of the commonly used anti-microbials it is of utmost importance to carry out regular surveillance of bacterial profile and their anti-microbial susceptibilities to formulate updated guidelines for effectively treating urinary infections in diabetic patients.